2020
DOI: 10.1186/s12967-020-02657-6
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells therapy enhance immunoregulatory properties in acute graft versus host disease with combination of regulatory T cells

Abstract: Background Myeloid-derived suppressor cells (MDSCs) play a critical role in modulating the immune response and promoting immune tolerance in models of autoimmunity and transplantation. Regulatory T cells (Tregs) exert therapeutic potential due to their immunomodulatory properties, which have been demonstrated both in vitro and in clinical trials. Cell-based therapy for acute graft-versus-host disease (aGVHD) may enable induction of donor-specific tolerance in the preclinical setting. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The induction of tolerance to exogenous antigens by IL-10 + Bregs has been further explored in the field of allograft transplantation. Studies in a model of hematopoietic stem cell transplantation (HSCT) demonstrated that both donor and host IL-10-producing B cells are required to prevent acute and chronic GVHD, in part due to the suppression of T cell cytokine production and induction of Tregs ( 37 , 116 , 262 264 ). Similarly, a protective role of IL-10 + Bregs in human GVHD has been suggested after higher frequencies of these cells were found reconstituting recipients of HSCT who developed tolerance, compared to those who developed GVHD ( 53 , 138 , 265 , 266 ).…”
Section: Suppressive Mechanisms Of Bregs By Soluble Moleculesmentioning
confidence: 99%
“…The induction of tolerance to exogenous antigens by IL-10 + Bregs has been further explored in the field of allograft transplantation. Studies in a model of hematopoietic stem cell transplantation (HSCT) demonstrated that both donor and host IL-10-producing B cells are required to prevent acute and chronic GVHD, in part due to the suppression of T cell cytokine production and induction of Tregs ( 37 , 116 , 262 264 ). Similarly, a protective role of IL-10 + Bregs in human GVHD has been suggested after higher frequencies of these cells were found reconstituting recipients of HSCT who developed tolerance, compared to those who developed GVHD ( 53 , 138 , 265 , 266 ).…”
Section: Suppressive Mechanisms Of Bregs By Soluble Moleculesmentioning
confidence: 99%
“…Although natural MDSCs increase their number in inflammation, their immunosuppressive activity might be limited in a highly inflammatory environment due to myeloid differentiation, inflammatory mediator production, and cellintrinsic inflammasome upregulation (41). Nevertheless, researchers have found that in vitro-induced MDSCs after culturing BM cells with G-CSF and GM-CSF obtained a phenotype similar to that of natural MDSCs with a protective effect in various primary target organs and inhibited GVHDcorrelated death by 80% (42,43). This indicated the potent treatment efficiency of adoptive transference of MDSC-enriched populations after in vitro expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Treg can inhibit the activation and proliferation of CD4 + and CD8 + T lymphocytes, which is related to the direct contact between cells and paracrine cytokines IL-10 and TGF-β [ 18 ]. Interleukin-2 (IL-2) and other immunoregulatory molecules have been shown to control the generation of Tregs [ 19 ]. It can also indirectly inhibit the immune response by inhibiting the activity of APC while maintaining the microenvironment of immune tolerance.…”
Section: Discussionmentioning
confidence: 99%